Adherence and acceptability of community‐based distribution of micronutrient powders in Southern Mali. (17th October 2019) - Roschnik, Natalie; Diarra, Hawa; Dicko, Yahia; Diarra, Seybou; Stanley, Isobel; Moestue, Helen; McClean, Judy; Verhoef, Hans; Clarke, Sian E.
Abstract: Home fortification with micronutrient powders (MNP) has been shown to reduce anaemia, with high overall acceptability and adherence, but there is limited evidence from West Africa. Around 80% of children younger than 5 years are anaemic in Mali, and new interventions are needed. This paper reports on the adherence and acceptability of a community‐led MNP intervention targeting children aged 6–59 months in Southern Mali. The MNP were delivered by a multidisciplinary group of community volunteers using community‐based preschools, cooking demonstrations, and traditional communication networks to promote MNP, nutrition, hygiene, and child stimulation. The MNP were delivered alongside early childhood development interventions and seasonal malaria chemoprevention. Adherence and acceptability were evaluated through two cross‐sectional surveys in 2014 and 2016 and a qualitative evaluation in 2015. Over 80% of parents reported ever having given MNP to their child, with 65% having given MNP for four or more days in the last week. Likely contributors to uptake include: perceived positive changes in the children following MNP use, the selection of a food vehicle that was already commonly given to children (morning porridge or bouillie) and the community driven, decentralized and integrated delivery approach. These findings support recommendations from recent reviews of MNP implementation to use community‐based delivery approaches and behaviour change components.